KONDISI OPTIMUM PEMBENTUKAN KOMPLEKS ION LOGAM Cr(III) DAN Mn(II) DENGAN 8-HIDROKSIKUINOLIN MENGGUNAKAN SPEKTRONIK - Mutiara Oksyarni; Budhi Oktavia (Departemen Kimia FMIPA UNP, 2019)
Industrial development will generate waste containing hazardous chemical substances one of heavy metal. Heavy metals are commonly used are chromium and manganese. Contamination of heavy metals in water is an environmental problem throughout the world because water is a source of life for all living beings .The purpose of this study is to look at the optimum condition of Cr(III) and the ion Mn(II) with oxine as a complexing agent for metal ion analysis using Spectronic. Determination of optimum conditions is to the optimum stirring time variation of the formation of complex compounds, variation the concentration and pH of the sample, then determination the time of stability of the formation of complex compounds. These results indicate that the complex compounds the Cr(III)-Oxinate and Mn(II)-Oxinate produce yellow complex. The optimum stirring time of complex formation of Cr(III)-Oxinate is 20 minutes with the optimum concentration of 20 ppm at optimum pH is pH 6 complex formation and stability of the complex at the time they reach the 40 minute. While Mn(II)-Oxinate have optimum stirring time 15 minutes with the optimum concentration of 15 ppm at optimum pH complex formation is pH 4 and reach a stability of the complex in the 45 minute.